Three by the sea - Grey, Mini (Alfred A. Knopf, 2010)
Cat, Dog, and Mouse live together contentedly in a cottage by the sea, dividing the work between them, until A. Stranger, Esq., a fox from the Winds of Change company, arrives and stirs up trouble.